Application of carbon nano-materials in desalination processes - Zaib, Qammer (2013)
Scarcity of freshwater resources increases the importance of seawater and brackish water desalination processes. However, still, large amount of specific energy requirement, leading to high operational costs, presents a big challenge in adopting desalination technologies. This challenge can be addressed by considering the newly emerging nanomaterials especially those made from carbon. This paper presents a comprehensive literature survey and review that brings those carbon nano-materials (CNMs) into focus which directly participate in desalination processes. The structural and functional properties of CNMs, their fabrication into membranes, their formation into bucky papers, and their composite electrodes are some of their usages in desalination processes which are exploited. The survey and analysis of the available literature shows that CNMs can enhance capacity and efficiency of next generation desalination systems, particularly reverse osmosis, membrane distillation, capacitance deionization, and forward osmosis.